Work-Life Balance, Job Demands, and Burnout - Maghfira, Naya Astri; Suyasa, P. Tommy Y. S.; Budiana, I Made (Jurnal Locus Penelitian dan Pengabdian, 2025)
Work-life balance refers to the equilibrium between work and personal life, characterized by company support in resolving family issues, opportunities to pursue hobbies outside of work, and availability of time for family. Job demand is an individual's perception of work-related demands, such as heavy workloads, tight deadlines, and requirements to display specific emotional states (calm, friendly, etc.). Burnout is a condition of stress marked by feelings of emotional exhaustion (easily irritated/angry), depersonalization (indifference toward others' conditions), and a sense of incompetence in completing tasks/work. High job demand tends to increase the likelihood of burnout. This study aims to test the work-life balance model as a resource that can anticipate and prevent job demands from leading to burnout. The participants in this study consisted of 114 employees. The instruments used in the research include the Maslach Burnout Inventory, the Job Demands-Resources Questionnaire, and the Quality of Work-Life Scale. Based on the analysis using Spearman Correlation, the results indicate that work-life balance can predict lower perceptions of job demands. Lower perceptions of job demands can, in turn, predict lower levels of burnout. The findings of this study provide a theoretical model that explains work-life balance as an antecedent that should be promoted to prevent stress, whether in the form of stimulus-based stress (job demand) or response-based stress (burnout).